Mycobacterium tuberculosis host adaptation and evolution reflected by defense mechanisms against oxidative stress - Mestre, Olga Maria Elviro, 1984- (2013)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2012